The Effectiveness of Learning to Write Poetry with The Student Team Achievement Division (STAD) Model (Journal of Primary Education, 2019)
Various problems in learning to write poetry are factors that trigger the low ability to write poetry for fifth grade students of SD Negeri in Kedungjati District. Problems experienced by students in learning to write poetry include teacher explanations that tend to be boring, motivation, difficult to express ideas, and the most problematic problems for students are learning models that tend to be monotonous. Effective learning models become one of the important factors for teachers or students in improving students' ability to write the poem. One learning model that can improve students' writing skills is Student Team Achievement Divisions (STAD) learning model, because the STAD model can collaborate several language skills, and requires students to work together in groups. The purpose of this research was to determine the effectiveness of learning to write poetry with the STAD model. This research uses a quasi-experimental method. The subject of this research was the fifth grade students of elementary school in Kedungjati Subdistrict 2017/2018 Academic Year. Data collection uses tests and non-tests. Data analysis techniques using t test with the help of SPSS program. The results of learning to write poetry between before and after being given learning to write poetry with the STAD model with the acquisition of t count = 7.848 with sig < 0.05. The results of this research indicate that learning to write poetry with the STAD model can effectively improve students' poetry writing skills.